Health services management in Turkey: Failure or success? - Bener, Abdulbari; Alayoğlu, Nihat; Çatan, Funda; Torun, Perihan; Şafak Yılmaz, Esra (Wolters Kluwer Medknow Publications, 2019)
Background: The unfair distribution and delivery of health-care resources have been recognized as a problem in the worldwide. In the past 18 years, Turkey has undergone rapid social, cultural, and economic changes. The lifestyle and dietary habits of its people have also been changing, and the rates of diabetes, obesity, cancer, and other chronic diseases have increased dramatically over the past two decades. The health transformation program (HTP) has improved the Turkish health-care system since 2003. The main goal of HTP was to progress government, to provide equality between citizens, to give satisfaction to users and providers, and to subsidise the health-care system in Turkey. Aim: The aim of this study is to assess health-care services and health care quality delivery in the Republic of Turkey with special emphasis on governmental hospitals, university hospitals, primary healthcare centers (PHC) and to make comparison with low-, medium- and high-income countries. Methods: This is a retrospective, descriptive study. The ministry of health Annual Reports, websites of the Central Intelligence Agency (CIA), The World Fact Book, organization for economic cooperation and development report, Compendium of Health Statistics, the Google engine, and PubMed were searched for information about Turkey's health-care system and its history. Papers and websites in English were evaluated. There was no restriction on types of articles and sources. Results: Turkey has made outstanding reforms in health status in the last two decades, especially after the implementation of the HTP. The doctor's perception has more influence regarding consultation length and visit than the patient's. The results of consultations in volunteer practices in Istanbul showed that the mean and SD of the consultation length for the whole sample of 360 patients was 7.95 +/- 4.38, (with range = 3-25 min). Consultation time has been affected by the patients' diseases, genders that women got longer consultation time, medical practices at the urban or rural areas, and ages which older patients required longer consultation time. The current study revealed that increasing doctor's workload leads to decrease the length of consultations. Moreover, average life expectancy reached 75.3 for men and 80.7 for women in 2015. The infant mortality rate decreased to 10.7/1000 live births in 2015, down from 117.5 in 1980. The leading causes of death are diseases of the circulatory system followed by cancer. Conclusions: The Turkish health system and health-care delivery have been improved over the last decade. Still far from perfect, there is a particular planning to increase medical workforce in PHC including well-trained staffs for a specific area. An urgent need is to acquire more accurate and reliable data from hospital and PHC centers in Turkey. Additional some attempts should be made to assess quality of healthcare in relation to services and process.
WOS: 000463098000003
PubMed ID: 30967916
Keywords: Assessment; Health Care Services; Health Performance; Management Ministry of Health; Turkey